Plan de emprendimiento de una agencia de marketing digital en la ciudad de Machala. - Valarezo Cajamarca, Jessica Carolina (My University, 2019)
The present project of entrepreneurship was based on a study to determine the feasibility and viability of the creation of a digital marketing agency specializing in the management of digital pages and digital tools (web page, social networks: Facebook and Instagram) for small and medium-sized enterprises (PYMES) of the city of Machala. At present, the management of digital tools has been increasing in a positive way in the domestic market, becoming a tool of information and recognition for many companies. In the city of Machala through the study of the competition gave as a result there are many agencies and independent persons who perform management of social networks in a professional manner, basic and empirical, because our market is in a state of transition between traditional and technological development. The process of the study was carried out in a quantitative and qualitative used these two methods of investigation, due to the quantitative research was obtained through secondary data with the purpose of knowing the number of small and medium-sized businesses existing in the city of Machala and increased use of technology companies, these data were collected from the digital platform of the National Institute of Statistics and Censuses of Ecuador. A qualitative study was based on the collection of information through interviews with recognized professionals of digital marketing city of Machala, who with their professional input and experience showed us that it is necessary to educate our customers on the use and the benefits that can be obtained with the use of different digital tools, In addition it is important to the communication that is obtained with the client using the correct channels such as direct communication and good development, through the implementation of the interviews more secondary school was structured the study of relevant market to develop a work plan that meets all the characteristics and needs of the customer. The service of the present project is to provide a complete and integrated advice in routing the strategic digital marketing and business together with the graphic visual and audio visual, focusing on the management and planning of strategies implemented direct marketing, positioning, sales, customer service, sales and business addressing post. In addition, we will have online presence in digital media such as: web page, social networks and search engines (SEO and SEM), where we will communicate with our customers by offering our services and promotional packages. Direct Messages and paid advertising in social networks. There will be a digital marketing event where they will present the company to Valdigital as a new marketing agency that offers community services manager in the city of Machala, where we will invite entrepreneurs, business owners of PYMES Within the financial feasibility is used indicated that express the economic performance through investment the TIR and VNP is high which indicates to us that our project of entrepreneurship is an act to run it or do it, where to contribute to social development, technological and economic development in the city of Machala.
El presente proyecto de emprendimiento se basó en un estudio para determinar la factibilidad y viabilidad de la creación de una agencia de marketing digital especializada en el manejo de páginas digitales y herramientas digitales (página web, redes sociales: Facebook e Instagram) para las pequeñas y medianas empresas (PYMES) de la ciudad de Machala. En la actualidad el manejo de las herramientas digitales ha ido incrementando de manera positiva en el mercado nacional, llegando a convertirse en una herramienta de información y de reconocimiento para muchas empresas. En la ciudad de Machala mediante el estudio de la competencia dio como resultado existen muchas agencias y personas independientes que realizan manejo de redes sociales de manera profesional, básica y empírica, debido que nuestro mercado se encuentra en un estado de transición entre lo tradicional y tecnológico. El proceso del estudio se realizó de manera cuantitativa y cualitativa se utilizaron estos dos métodos de investigación, debido a que la investigación cuantitativa se obtuvo mediante datos secundario con la finalidad de conocer el número de empresas pymes existentes en la ciudad de Machala y el incremento de uso de la tecnología de las empresas, estos datos se recopilaron de la plataforma digital del Instituto Nacional de Estadística y Censos del Ecuador. La cualitativa se basó en la recopilación de información mediante la realización de entrevistas a reconocidos profesionales del marketing digital ciudad de Machala, quienes con su aportación profesional y experiencia nos indicaron que es necesario educar a nuestros clientes sobre el uso y los beneficios que pueden obtener con el uso de las diferentes herramientas digitales, además que es importante la comunicación que se obtiene con el cliente utilizando los canales correctos como la comunicación directa y buen desenvolvimiento, mediante la realización de las entrevistas más los estudios secundarios se estructuro el estudio de mercado pertinente para desarrollar un plan de trabajo que cumpla todas las características y necesidades del cliente. El servicio que ofrece el presente proyecto es brindar una asesoría completa e integrada en el direccionamiento del marketing digital estratégico y empresarial junto con el área gráfica visual y audio visual, centrándonos en el manejo y planeación de estrategias implementado marketing directo, posicionamiento, ventas, servicio al cliente, post ventas y direccionamiento empresarial. Además, tendremos presencia online en medios digital como: página web, redes sociales y en los motores de búsqueda (SEO y SEM), donde nos comunicaremos con nuestros clientes ofreciéndoles nuestros servicios y paquetes promocionales. Mensajes directos y publicidad pagada en redes sociales. Se realizará un evento de marketing digital donde se presentará a la empresa Valdigital como una nueva agencia de marketing que ofrece servicios de community manager en la ciudad de Machala, donde se invitaran empresarios, dueños de negocios de las pymes. Dentro de la factibilidad financiera se utilizaron los indicaron que expresan el rendimiento económico a través de la inversión el TIR y VNP es alto que nos indica que nuestro proyecto de emprendimiento es acto para ejecutarlo o realizarlo, donde permitirá contribuir con el desarrollo social tecnológico y económico en la ciudad de Machala.
Keywords: MARKETING DIGITAL; COMMUNITY MANAGER; MARKETING DIRECTO; REDES SOCIALES; EMPRENDIMIENTO